Dynamic PDC and HMM-based asynchronous output feedback strict dissipative control for nonlinear singular incomplete jumping systems with actuator saturation - Sun, Meng; Zhuang, Guangming; Ma, Qian; Wang, Yanqian (Chaos, solitons and fractals, 2024)
This paper investigates the asynchronous output feedback strict dissipative control for nonlinear singular incomplete jumping systems with actuator saturation via dynamic parallel distributed compensation technique and hidden Markov model mechanism. Dynamic parallel distributed compensation technique is used to design the asynchronous fuzzy dynamic output feedback controller and hidden Markov model is employed to describe the asynchronous phenomenon between the singular Markov jump system modes and the dynamic output feedback controller modes. Novel conditions of stochastic admissibility and strict dissipativity for the fuzzy closed-loop singular Markov jump systems are derived based on singular value decomposition technique and improved L-K functional. The asynchronous dynamic output feedback controller gains are developed in terms of linear matrix inequalities and the minimization optimization scheme is proposed by established ellipsoid. Single-link robot arm simulation results illustrate the practicability and effectiveness of the proposed methods.